Deformity stabilization and improvement in men with untreated Peyronie's disease. (31st October 2013) - Berookhim, Boback M.; Choi, Judy; Alex, Byron; Mulhall, John P.
<x xml:space="preserve">Abstract</x> Objective To define predictors of the deformity stabilisation and improvement in men with untreated Peyronie's disease (PD). Patients and Methods The study population consisted of patients with PD‐associated uniplanar curvature, who opted for no treatment and were followed for at least 12 months. All patients had deformity assessment (DA) performed on initial presentation and at follow‐up. Stabilisation of PD was defined as no change between DAs (±10°), while improvement and progression were defined as ≥10° change. Patients were subdivided into different groups based on time to presentation: ≤6 months (A), 7–12 months (B), and 13–18 months (C). Multivariable analysis was used to define predictors of stabilisation and improvement. Results In all, 176 men met the inclusion criteria. The mean age was 54 years, with a mean (sd) PD duration of 9 (12) months and mean curvature of 42 (27)°. In all, 67% of the entire population had no change in deformity over time, 12% improved with a mean (sd) change of 27 (14)°, and 21% worsened with a mean (sd) change of 22 (11)°. On multivariate analysis, predictors of stabilisation included: time to presentation of >6 months (odds ratio [OR] 2.4, P < 0.01), per decade increase in age (OR 1.5, P < 0.05), and age (r = 0.32, P < 0.05). Predictors of improvement included: time to presentation of ≤6 months (OR 4.1, P < 0.001), and per decade decrease in age (OR 2.1, P < 0.01). Conclusions In men with uniplanar curvature, PD stabilisation and improvement rates change with time‐to‐presentation and patient age. These data may aid in counselling patients with PD.